The effect of ellagic acid on caspase-3/bcl-2/Nrf-2/NF-kB/TNF-? /COX-2 gene expression product apoptosis pathway: a new approach for muscle damage therapy - Aslan, Abdullah; Beyaz, Seda; Gok, Ozlem; Erman, Orhan (Springer, 2020)
The goal of this study was to determine the protective role of ellagic acid (EA) against CCl4-induced muscle injury in rats. In this study, 36 Wistar albino rats (n = 36, 8 weeks old) were used. The rats were divided into 4 groups and 9 rats were included each group. Groups: (i) control Group: standard diet; (ii) EA Group: standard diet + EA group; (iii) CCl4 group: standard diet + CCl4 group; (iv) EA + CCl4 group: standard diet + EA + CCl4. The animals were decapitated after 8 weeks, and their muscle tissues were received and investigated. In the muscle tissue, TNF-alpha, COX-2, Nrf-2, NF-kB, caspase-3 and bcl-2 expression levels were analyzed by the western blotting technique, lipid peroxidation was detected by MDA (malondialdehyde), and catalase and GSH levels were determined by a spectrophotometer. In our findings, in comparison to the CCl4 group, in the EA + CCl4 group, the Nrf-2 and caspase-3 protein expression levels, GSH and catalase activities increased, while the NF-kB, bcl-2, TNF-alpha and COX-2 protein expression levels and MDA levels decreased. These results suggest that EA reduces muscle tissue damage rate in rats and that EA may also be used as a potential drug to protect against muscle tissue damage in the future. Graphic abstract
Keywords: Bcl-2; COX-2; Ellagic acid; Muscle damage; NF-kB; Nrf-2; TNF-alpha